Guided wave propagation in structural health monitoring (Experimental Study) - Teo, Kian Yong. (2010)
This final year project investigates the feasibility of using smart material in the form of piezoelectric wafer active sensor (PWAS) to excite a structure in question. The PWAS type we are using in our experiments is the Lead Zirconate Titanate (PZT). The two main experiments conducted consist of a one-dimensional modeling case study of an aluminum strip and a two dimensional modeling case study of an aluminum plate. The use of PWAS for structural health monitoring (SHM) in non-destructive evaluation (NDE) follows three main paths: i) the modal analysis and transfer function, ii) the electromechanical impedance (EMI) method and iii) the guided wave propagation method. In this research, we focus solely on method iii), using ultrasonic guided wave propagation, Lamb wave propagation in particular, in order to obtain data plots in which the major modal frequency and mode shapes can be shown clearly. In the theory section of this report, we investigate the characteristics of the guided waves, i.e. Lamb waves, and the way it can be utilized in our experiments to acquire accurate structural identification, characterization and parametric interpretation of damages on a homogeneous specimen.